DISTRIBUTION OF CETACEANS IN THE SEA OF JAPAN (Rasprostranenie Kitoobraznykh v Yaponskom More) - Sleptsov,M. M. (1970)
The hydrological regime, including the current system and mixing of cold and warm waters is analyzed. This information provides a background for the distribution pattern of plankton and fishes. The distribution of whales is discussed on pages 107 and 108. There are 21 species of cetaceans in the Sea of Japan: 15 species of toothed whales (Odontoceti) and 6 species of baleen whales (Mystacoceti). Some of the small cetaceans form pods consisting of as many as 2000 individuals. The populations of the larger hales are decreasing. During 1911-1915 as many as 120-185 gray whales were killed each season by Japanese whalers; but in 1930 the catches had decreased to 50. (Author) Trans. of Akademiya Nauk SSSR. Institut Morfologii Zhivotnykh. Trudy, v34 p93-110 1961, by M. Slessers.